New Role of Adult Lung c-kit+ Cells in a Mouse Model of Airway Hyperresponsiveness - Giuseppe Spaziano; Donato Cappetta; Konrad Urbanek; Elena Piegari; Grazia Esposito; Maria Matteis; Manuela Sgambato; Gioia Tartaglione; Rosa Russo; Raffaele De Palma; Francesco Rossi; Antonella De Angelis; et al. (Hindawi Limited, 2016)
Structural changes contribute to airway hyperresponsiveness and airflow obstruction in asthma. Emerging evidence points to the involvement of c-kit+ cells in lung homeostasis, although their potential role in asthma is unknown. Our aim was to isolate c-kit+ cells from normal mouse lungs and to test whether these cells can interfere with hallmarks of asthma in an animal model. Adult mouse GFP-tagged c-kit+ cells, intratracheally delivered in the ovalbumin-induced airway hyperresponsiveness, positively affected airway remodeling and improved airway function. In bronchoalveolar lavage fluid of cell-treated animals, a reduction in the number of inflammatory cells and in IL-4, IL-5, and IL-13 release, along with an increase of IL-10, was observed. In MSC-treated mice, the macrophage polarization to M2-like subset may explain, at least in part, the increment in the level of anti-inflammatory cytokine IL-10. After in vitro stimulation of c-kit+ cells with proinflammatory cytokines, the indoleamine 2,3-dioxygenase and TGFβ were upregulated. These data, together with the increased apoptosis of inflammatory cells in vivo, indicate that c-kit+ cells downregulate immune response in asthma by influencing local environment, possibly by cell-to-cell contact combined to paracrine action. In conclusion, intratracheally administered c-kit+ cells reduce inflammation, positively modulate airway remodeling, and improve function. These data document previously unrecognized properties of c-kit+ cells, able to impede pathophysiological features of experimental airway hyperresponsiveness.